Systematic Review: Heat Treatments on Phenolic Content, Antioxidant Activity, and Sensory Quality of Malaysian Mushroom: Oyster (Pleurotus spp.) and Black Jelly (Auricularia spp.) - Izham, Inshirah; Avin, Farhat; Raseetha, Siva (Frontiers in Sustainable Food Systems, 2022)
Pleurotus spp. and Auricularia spp. were popular species consumed by Malaysian community. Besides of their nutrient-rich content, both mushrooms also well known for its bioactive compounds, ergothioneine and antioxidant properties and has been used since earlier ages as therapeutic remedies. The bioactive compounds such as phenol, flavonoid and ergothioneine found in both Pleurotus and Auricularia mushrooms were explored. Indisputable fact of high temperature exposed during cooking or food processing affect this bioactive compounds values and its properties as well as sensory quality also included. DPPH (1,1- diphenyl-2-picryl-hydrazyl) radical and FRAP (ferric reducing antioxidant power) assay from studies were appended to found out antioxidant properties of both raw and heat-treated mushrooms. Effect of microwave, hot air drying and solar drying on the phenolic content, flavonoid, ergothioneine, antioxidant properties and sensory quality of both mushrooms were the main discussion of this study. To add values into this review, survey on consumption pattern of Pleurotus and Auricularia species among Malaysian has been conducted through online and concluded that Pleurotus species is most considered species compared to Auricularia mushroom and almost half of the respondents did not aware heat may deplete nutritional contents in mushroom despite they agreed both gave beneficial health in diets.